Bucket Effect to Improve Third‐Order Nonlinear Optical Response on Metal‐Heteroaromatic Compounds. Issue 22 (23rd August 2022) - Wang, Zirui; Fang, Yu‐Hui; Lin, Huaxing; Zhao, Guoxiang; Yan, Weiyin; Ma, Zuju; Li, Qiao‐Hong; Zhang, Jian
Comprehensive Summary: Carbolong compounds as a metal‐heteroaromatic compound with both organometallic properties and π‐conjugated systems exhibit great potential in organic catalysis and optoelectronic devices. In this work, for the first time, the "Bucket Effect" is revealed to promote the third‐order nonlinear optical (NLO) performance in metal‐heteroaromatic compounds. We have successfully constructed and investigated a series of novel metallapentalenes with higher third‐order NLO performance benefited from the "Bucket Effect". Meanwhile, aromaticity and electron−hole analysis further confirm the internal homogeneity of organometallic rings, reduced bandgap, and enhanced low‐energy peak response resulted in the enhanced third‐order NLO effects. The success of this work is discovering an emerging material library of high third‐order NLO effects, and illustrating the feasibility of engineering the high response metal‐heteroaromatic optical devices at the electronic structure level. Abstract : "Bucket Effect" is revealed to promote the third‐order nonlinear optical performance in metal‐heteroaromatic compounds due to the internal homogeneity of organometallic rings.